Synthesis and Characterization of ZnO with Calcination Temperature Variation and Surfactant Addition using Chemical Coprecipitation Method - Charlena Charlena; Sri Sugiarti; Yemima Chellyne Khefanny (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
This study aims to synthesize ZnO using the coprecipitation method and characterize it using various instrumentation techniques. The calcination temperature variation treatment was carried out to produce particles with good size and crystallinity levels. Adding polyvinyl pyrrolidone (PVP) surfactant during the synthesis of ZnO aims to prevent agglomeration. ZnO characterization used ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), Fourier transform spectroscopy (FTIR), and scanning electron microscopy (SEM). The result showed that the value of the ZnO band gap increased with increasing temperature. ZnO synthesized at a calcination temperature of 800 Â°C has a hexagonal wurtzite structure. The crystal size of ZnO is 45.64 nm, while ZnO-PVP's is 40.37 nm. The best ZnO crystallinity level is 61.34%. The FTIR spectrum shows ZnO absorption in the fingerprint region (525 cm-1). SEM micrographs showed that ZnO without the addition of PVP agglomerated. The synthesized ZnO has an antibacterial activity, indicated by forming an inhibition zone (7.84 mm